Maldives Debt Management Reform Plan - World Bank (World Bank, Washington, DC, 2020)
The first Debt Management Performance Assessment (DeMPA) for Maldives was conducted in 2009, and a second DeMPA was completed in March 2019. The authorities have taken important steps to improve debt management since the first assessment, but many challenges remain. The government has implemented a series of reforms to public financial and debt management, including changes to the legal and institutional framework. Key measures include a complete overhaul of Treasury operations, the implementation of the Integrated Financial Management Information System (IFMIS) across all government entities in the capital, Malé, the establishment of a Treasury Single Account, and the development of cash-flow forecasting procedures. The coverage of the Commonwealth Secretariat Debt Recording and Management System (CSDRMS) has also been expanded, and the CS-DRMS is now used as a central database for almost all debt obligations, except Islamic finance instruments. The results of the 2019 DeMPA shed light on these improvements and indicate areas for further action.